Antimicrobial power of biosynthesized Ag nanoparticles using refined Ginkgo biloba leaf extracts - ZHUANG, Wenbo; HU, Dafeng; ZHANG, Xudong; XIONG, Kai; DING, Xiao; LU, Jian; MAO, Yong; YANG, Peng; LIU, Chao; WAN, Yanfen (Frontiers of materials science, 2022)
Silver nanoparticles (Ag NPs), relative to existing antibacterial agents, are more effective, less toxic and more economical, and have shown enormous potential for the nanomedicine application. In this work, we report a 'green' method for the rapid and efficient synthesis of Ag NPs using Ginkgo biloba extracts as reducing agent and capping agent. The properties of Ag NPs against fungi and bacteria were investigated. The results showed that the Ginkgo biloba extracts are crucial for the preparation of uniform and monodispersed Ag NPs. The prepared Ag NPs exhibited remarkable antibacterial activities. The minimum inhibitory concentrations of Ag NPs for Escherichia coli and Pseudomonas aeruginosa were 0.044 and 0.088 μg·mL −1, respectively. Moreover, Ag NPs exhibited excellent bactericidal performance against MDR- Pseudomonas aeruginosa. It was found that the effect of the antibacterial activity of Ag NPs on Escherichia coli and Staphylococcus aureus was tightly related to the reactive oxygen species accumulation. This research provides guidelines for the efficient green synthesis of Ag NPs and its antibacterial applications.